Upaya Guru Bimbingan dan Konseling dan Ustadz/Ustadzah dalam Menangani Siswa yang Melanggar Tata Tertib Sekolah di SMP Insan Kamil Bogor - Riskiyah, Fifin Naili (Program Studi Bimbingan dan Konseling Islam, 2022)
School rules that must be obeyed by all students sometimes there are still students who do not obey them. The existence of this research aims to find out the efforts made by the BK teacher and ustadz/ustadzah overcoming students who violate school rules. Based on the research conducted, the formal forms of business carried out by counseling teachers are orientation services, information services, group and individual guidance services, while the formal forms of business carried out by ustadz/ustadzah are modeling and providing guidance. Informal forms of business are in the form of exchanging information between the guidance counselor and ustadz/ustadzah and granting permission/authority for the guidance counselor/ustadzah to the counseling teacher if he wants to carry out the duties of the ustadz/ustadzah. So indeed between the BK teacher and ustadz/ustadzah must work together in an effort to deal with students who violate school rules